All things bright and beautiful - Herriot, James (New York St. Martin's Press, 1974)
Now in a new edition for the first time in a decade, All Things Bright and Beautiful is the beloved sequel to Herriot's first collection, All Creatures Great and Small, and picks up as Herriot, now newly married, journeys among the remote hillside farms and valley towns of the Yorkshire Dales, caring for their inhabitants---both two- and four-legged. Throughout, Herriot's deep compassion, humor, and love of life shine out as we laugh, cry, and delight in his portraits of his many, varied animal patients and their equally varied owners.
Keywords: Herriot, James; Veterinarians -- England -- Yorkshire -- Biography